Axial Vascularization of Nano-HA/Collagen/PLA Composites by Arteriovenous Bundle. (17th July 2013) - Wang, Hai; Chang, Xiao; Qiu, Guixing; Cui, Fuzhai; Weng, Xisheng; Zhang, Baozhong; Yang, Bo; Lian, Xiaojie; Wu, Zhihong
Abstract : In previous studies, nano-hydroxyapatite/collagen/poly(L-lactic acid) (nHAC/PLA) composites have been prepared and confirmed to repair small sized bone defects. However, they are restricted to repair a large defect without sufficient oxygen and nutrition for cell survival. The result of this study confirmed that nHAC/PLA composites could be axially vascularized by being implanted intramuscularly with arteriovenous (AV) bundle (Group A) in the groins of rabbits. The combination with autologous bone marrow (Group B) could not enhance it the vascularization in early phase (2 weeks, P > 0.05 ), but it could enhance in middle and later phases (6 and 10 weeks, P < 0.01 ). It meant that nHAC/PLA could be prefabricated as a vascularized bone substitute for grafting.